Znamiona przestępstw z art. 256 § 1–2 k.k. - Budyn-Kulik, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The issue of the scope of criminalization under Article 256 of the Polish Penal Code is important in the age of a rise in popularity of totalitarian ideologies. Currently, this proviso contains three basic types of prohibited acts, which themselves are multi-variate and complex. The article offers an analysis of selected features, primarily new ones, introduced by the amendment of July 7, 2022, or those that have so far received less attention. These include subjective premises. All types contain feature pertaining to motivation, which means that, as a rule, they can only be committed intentionally with direct or direct intention. The provision of Article 256 PCC still raises some controversy and will probably be subject to further amendments by the legislator.
Keywords: prawo karne; faszyzm; totalitaryzm; nienawiść